DAMPAK KEBUTUHAN SOSIAL, PENGHARGAAN, DAN KEBUTUHAN AKTUALISASI DIRI TERHADAP PRESTASI BELAJAR ANGGOTA HMJM UNIVERSITAS ISLAM MALANG - Naufal Rifqi Syafruddin; Nur Hidayati; Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine and analyze the influence of social needs, appreciation, and self-actualization needs on the learning achievement of members of the Islamic Student Association of Malang Islamic University. In this study the data collection method used a questionnaire method (questionnaire). The type of data used in this study is primary data. The method of analysis used in this research is multiple linear regression. This study uses data from a questionnaire distributed to members of the HMJM Islamic University of Malang and the sample is taken using purposive sampling. The number of samples taken was 64 respondents The results showed that social needs had no effect on learning achievement. While rewards and self-actualization needs affect learning achievementKeywords: Social Needs, Appreciation, Self Actualization Needs, Learning Achievement